Parasites Are Associated With Noisy Alarm Calls - Nouri, Kimia; Blumstein, Daniel T. (Frontiers in Ecology and Evolution, 2019)
Many animal signals used for mate choice assessment are condition dependent, but less is known about the condition dependence of other biologically important signals. We asked whether yellow-bellied marmot (Marmota flaviventer) alarm calls varied as a function of parasite infection and/or neutrophil:lymphocyte ratios (a measure of immunological challenge). We found that marmots infected with Eimeria, an intestinal parasite, had noisier calls. This is potentially because of an immunostimulating effect of Eimeria infection which may draw energy from nonvital functions. The results suggest calls potentially contain information about parasite status which could be used by receivers to estimate a caller’s condition. Future studies are required to determine whether infection influences caller reliability and how receivers respond to alarm calls from parasitized individuals.